A triple-blinded randomized trial comparing spinal morphine with posterior quadratus lumborum block after cesarean section. (November 2019) - Tamura, T.; Yokota, S.; Ando, M.; Kubo, Y.; Nishiwaki, K.
Highlights: Posterior quadratus lumborum block was used with or without spinal morphine. Spinal morphine improved postoperative analgesia after cesarean section. The combination of pQLB with spinal morphine did not provide analgesia. Abstract: Background: This study aimed to compare the postoperative analgesic effects of ultrasound-guided posterior quadratus lumborum block with spinal morphine, after cesarean section, using the visual analogue scale pain score. Methods: One-hundred-and-seventy-six pregnant women scheduled for elective cesarean section with spinal anesthesia were randomly allocated into four groups to receive spinal morphine 0.1 mg (group M + ); spinal saline (M − ); posterior quadratus lumborum block using either 0.3% ropivacaine (0.45 mL/kg each side, maximum 150 mg) group pQ + ); or saline (pQ − ). All patients received 11–13 mg hyperbaric bupivacaine 0.5% and 10 μg fentanyl. Intravenous droperidol, fentanyl and acetaminophen were administered during surgery. Bilateral posterior quadratus lumborum block was performed immediately after surgery. Postoperative pain was assessed at 0.5, 1, 2, 4, 6, 18 and 24 h after surgery, and the pain score 6 h after surgery was the primary endpoint. Results: One-hundred-and-forty-six patients were included in the final analysis. Pain scores 6 h after surgery, both at rest and when moving, were significantly different when comparing the M + pQ + group with the M − pQ + or M − pQ − groups, and when comparing the M + pQ − group with the M − pQ + or M − pQ − groups (all P <0.05). There was no significant difference between the M + pQ + and M + pQ – groups, or between the M − pQ + and M − pQ − groups. Conclusion: Spinal morphine improved postoperative analgesia but the combination of posterior quadratus lumborum block with spinal morphine did not lead to further improvement.